PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI MEUBEL DI RAFFA MEUBEL PASIR PENGARAIAN - Bar, Sani (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This study aims to determine the effect on the brand image in the consumer's decision to buy furniture in Raffa Meubel Sand Pengaraian. The study population is the entire consumer Raffa Furniture totaling 213 people and to determine the magnitude of the sample using the formula Slovin the number sebayak 68 respondents and the sampling technique is random sampling. Analysis of the data using a questionnaire with Likert scale measurement and testing using simple linear regression. Based on the test results show the value of R2 = 0.401 indicates that the influence of brand image on purchase decisions in at 40.10% and the remaining 59.90% influenced by other factors not examined, such as price, product quality and others. It was suggested to be a concern in improving the brand image, the variables that influence the perception of consumers to buy products. More and more consumers perceive positive increase sales. One way to improve the brand image in terms of indicators of this study need to improve consumer confidence in the brand